Járási polgári védelmi gyakorlat . Civil defense exercise in the district (Kinostudiia Ministerstva Oborony SSSR, 1974)
Soviet propaganda film, "V edinom stroiu", adapted by the Hungarian Civil Defense Alliance. The Soviet people has been busy building a peaceful future, knowing that friendship between the nations is the best guarantee for peaceful coexistence. However, no matter how hard we work to avoid a future war cannot, the possibility of a conflict cannot be excluded. For this reason, the Soviet Union makes strenuous efforts to improve its battle readiness. Civil defense, along with the task of preparing the civilian population, has strategic importance in this work. The film captures the exercise of the Soviet civil defense forces. A szovjet nép békés alkotómunkával tölti idejét, tudván, a népek közti barátság garantálja a békés egymás mellett élést. A háború elkerülésére tett erőfeszítések azonban nem zárják ki a konfliktus létrejöttét. Éppen ezért a Szovjetunió nagy figyelmet fordít a harckészültség növelésére. Ebben a felkészülésben stratégiai jelentőséget kap a polgári védelem, valamint a lakosság felkészítése. A film a szovjet polgári védelmi alakulatok gyakorlatát mutatja be.